Evaluation of lens absorbed dose with Cone Beam IGRT procedures. (12th October 2015) - Palomo, R; Pujades, M C; Gimeno-Olmos, J; Carmona, V; Lliso, F; Candela-Juan, C; Vijande, J; Ballester, F; Perez-Calatayud, J
Abstract: The purpose of this work is to evaluate the absorbed dose to the eye lenses due to the cone beam computed tomography (CBCT) system used to accurately position the patient during head-and-neck image guided procedures. The on-board imaging (OBI) systems (v.1.5) of Clinac iX and TrueBeam (Varian) accelerators were used to evaluate the imparted dose to the eye lenses and some additional points of the head. All CBCT scans were acquired with the Standard-Dose Head protocol from Varian. Doses were measured using thermoluminescence dosimeters (TLDs) placed in an anthropomorphic phantom. TLDs were calibrated at the beam quality used to reduce their energy dependence. Average dose to the lens due to the OBI systems of the Clinac iX and the TrueBeam were 0.71  ±  0.07 mGy/CBCT and 0.70  ±  0.08 mGy/CBCT, respectively. The extra absorbed dose received by the eye lenses due to one CBCT acquisition with the studied protocol is far below the 500 mGy threshold established by ICRP for cataract formation (ICRP 2011 Statement on Tissue Reactions ). However, the incremental effect of several CBCT acquisitions during the whole treatment should be taken into account.